2020
DOI: 10.3389/fonc.2020.00422
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Biological Advances Into the Clinical Management of Breast Cancer Related Lymphedema

Abstract: Breast cancer-related lymphedema (BCRL) occurs in a significant number of breast cancer survivors as a consequence of the axillary lymphatics' impairment after therapy (mainly axillary surgery and irradiation). Despite the recent achievements in the clinical management of these patients, BCRL is often diagnosed at its occurrence. In most cases, it remains a progressive and irreversible condition, with dramatic consequences in terms of quality of life and on sanitary costs. There are still no validated pre-surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 109 publications
(140 reference statements)
0
17
0
2
Order By: Relevance
“…Protection from pathogens may be compromised in cancer patients for whom radiation, chemotherapy, surgery or effects induced by the cancer itself lead to immunosuppression [ 24 – 28 ]. Immunity, specifically cell-mediated immunity, is critical for defence against some types of tumours and has been shown to be decreased in metastatic breast cancer patients, related to a dysfunctional HPA axis (our central stress response system) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protection from pathogens may be compromised in cancer patients for whom radiation, chemotherapy, surgery or effects induced by the cancer itself lead to immunosuppression [ 24 – 28 ]. Immunity, specifically cell-mediated immunity, is critical for defence against some types of tumours and has been shown to be decreased in metastatic breast cancer patients, related to a dysfunctional HPA axis (our central stress response system) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies in cancer patients have demonstrated that physical activity and exercise correlate with an improved outcome regarding the course of the underlying disease and with a better tolerance to the antineoplastic treatments ( 13 ). For example, exercise had positive effects on the fatigue syndrome and quality of life in cancer ( 12 , 14 ), the course of lymphedema ( 13 , 15 ) and osteoporosis in breast cancer ( 16 ) and prostate cancer ( 17 ). Moreover, physical activity influences various functions of the immune system, such as the proportions of circulating leukocyte subsets and the expression of cytokines ( 4 , 18 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…This chronic condition most commonly occurs in the lower extremities (legs and feet) [ 14 ]. The precise arm volume measurement allows the early detection of the interstitial accumulation of liquid and could reduce the incidence of irreversible stages [ 15 ]. Several methods were proposed in the literature to evaluate and monitor the upper and lower limbs lymphedema.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the 3DLS detects extremely small variations of volume including the presence and reduction of gibbousness and swelling (e.g., a consequence of bandages, press therapy, manual lymph drainage) [ 25 ]. The lymphoscintigraphy provides an objective measurement and adequately characterizes the severity of lymphedema [ 15 ]. In fact, this imaging technique allows the regional lymph nodes visualization and deep lymphatic nodes localization; nevertheless, this approach is difficult to be applied in the common clinical practice [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation